Field‐testing the new anaphylaxis' classification for the WHO International Classification of Diseases‐11 revision. Issue 5 (24th January 2017) - Tanno, L. K.; Molinari, N.; Bruel, S.; Bourrain, J.‐L.; Calderon, M. A.; Aubas, P.; Demoly, P.; ,
Abstract: Background: To consolidate the new classification model addressed to the allergic and hypersensitivity conditions according to the International Classification of Diseases (ICD)‐11 revision timeline, we here propose real‐life application of quality assurance methodology to evaluate sensitivity and accuracy of the 'Anaphylaxis' subsection. Methods: We applied field‐testing methodology by analysing all the consecutive inpatients' files documented as allergies from the University Hospital of Montpellier electronic database for the period of 1 year. The files clinically validated as being anaphylaxis were manually blind‐coded under ICD‐10 and current ICD‐11 beta draft. The correspondence of coding and the impressions regarding sensibility were evaluated. Results: From all 2318 files related to allergic or hypersensitivity conditions, 673 had some of the anaphylaxis ICD‐10 codes; 309 files (46%) from 209 patients had anaphylaxis and allergic or hypersensitivity comorbidities description. The correspondence between the two coders was perfect for 162 codes from all 309 entities (52.4%) (Cohen‐kappa value 0.63) with the ICD‐10 and for 221 codes (71.5%) (Cohen‐kappa value 0.77) with the ICD‐11. There was a high agreement regarding sensibility of the ICD‐11 usability (Cohen‐kappa value 0.75). Conclusion: We here propose the first attempt of real‐life application to validate the new ICD‐11 'Anaphylaxis' subsection. Clearer was the improvement in accuracy reaching 71.5% of agreement when ICD‐11 was used. By allowing all the relevant diagnostic terms for anaphylaxis to be included into the ICD‐11 framework, WHO has recognized their importance not only to clinicians but also to epidemiologists, statisticians, healthcare planners and other stakeholders.